Analisis LMTD dan Efektivitas terhadap Kinerja Pendinginan pada Desain Motor BLDC 5 kW Tipe Fluks Aksial Magnet Permanen Menggunakan Simulasi CFD - Riezky Hidayattullah; Dori Yuvenda; Yolli Fernanda; Andre Kurniawan (Unversitas Negeri Padang, 2025)
Axial flux type BLDC motors primary issue is the high operating temperature of the stator and winding components, which can lower system efficiency and hasten the deterioration of the quality of the insulation material. This study is to examine the effects of geometric alterations to the cooling system, such as axial fins on the housing side and curved fins on the casing, on the temperature distribution of a 5-kW axial flux permanent magnet BLDC motor. Convection and conduction heat transport in the cooling system were modeled using ANSYS Fluent software and computational fluid dynamics (CFD) simulation techniques. The Log Mean Temperature Difference (LMTD) and the cooling design's relative efficacy in comparison to the baseline state are the primary metrics that are examined. According to the simulation results, the maximum winding temperature may be lowered to 311 K and the cooling distribution in the rotor, casing, and housing can be improved by adopting curved fin casing and axial fin housing. As the temperature differential between the coolant and the motor surface narrows, the LMTD value drops from the initial condition (5.10 K to 13.94 K), suggesting a more effective heat transfer process. Furthermore, the cooling system's efficiency has more than doubled since its original design. Overall, the study's findings demonstrate that enhancing the cooler's geometric design can increase the BLDC motor's thermal performance and prolong component life.